(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
IoT deals with interconnection of devices and LiFi is a medium to achieve networking. Hence Light Fidelity (Li-Fi) is the biggest facilitator of IoT and Big Data. Li-Fi is a wireless technology which enables bi-directional and high speed data transfer. LiFi could be installed anywhere users might like light and data services bus shelters, train stations, street lights, tourist information kiosks could all provide data transmission as well as light. As the market for IoT devices grows and sensors are added to more and more things and places, faster and heavier data transmission will be required. Our current infrastructure simply cannot handle the quantity of data that will need to be transmitted if the IoT continues to grow at predicted rates. LiFi may be the only viable solution if we want Big Data and the IoT to continue to grow.